2021
DOI: 10.1371/journal.pone.0247274
|View full text |Cite
|
Sign up to set email alerts
|

Assessing sub-regional-specific strengths of healthcare systems associated with COVID-19 prevalence, deaths and recoveries in Africa

Abstract: Introduction The coronavirus 2019 (COVID-19) has overwhelmed the health systems of several countries, particularly those within the African region. Notwithstanding, the relationship between health systems and the magnitude of COVID-19 in African countries have not received research attention. In this study, we investigated the relationship between the pervasiveness of the pandemic across African countries and their Global Health Security Index (GHSI) scores. Materials and methods The study included 54 countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
3
18
0
1
Order By: Relevance
“…Taking into account that no country was adequately prepared for such a quickly spreading pandemic, the consequences of this outbreak have challenged the sustainability of healthcare systems, even in developed countries [ 2 ]. In Africa, the pandemic has been projected to be devastating due to the continent’s poor health systems, gaps in medical infrastructure, and vulnerability to infectious diseases [ 3 , 4 ]. However, the COVID-19 infection rates in African countries are now significantly lower than in other continents.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account that no country was adequately prepared for such a quickly spreading pandemic, the consequences of this outbreak have challenged the sustainability of healthcare systems, even in developed countries [ 2 ]. In Africa, the pandemic has been projected to be devastating due to the continent’s poor health systems, gaps in medical infrastructure, and vulnerability to infectious diseases [ 3 , 4 ]. However, the COVID-19 infection rates in African countries are now significantly lower than in other continents.…”
Section: Introductionmentioning
confidence: 99%
“…Study participants from the middle zone (e.g., Ashanti, Brong-Ahafo, Western North Regions) of Ghana were 2.3 times more likely to take mandatory COVID-19 vaccine than their counterparts from the southern zone (e.g., Greater Accra, Eastern and Volta Regions). Geo-spatial metrics (e.g., population density) could possibly explain the current observation [53,54]. Previous research has shown that vaccination rates may suffer amongst varied population groups, especially in areas of deprivation [55,56,57].…”
Section: Discussionmentioning
confidence: 83%
“…The COVID‐19 pandemic has affected many healthcare workers and has overwhelmed many healthcare systems, especially in sub‐Saharan Africa. 17 The morbidity and mortality rates of the virus coupled with the associated lack of resources at many healthcare centers in Ghana are likely to create a high sense of insecurity in terms of contracting the COVID‐19 virus for frontline healthcare workers. The high perceived risk of contracting the COVID‐19 virus when not managed properly causes substantial fear, panic, anxiety, and burnout among these healthcare workers.…”
Section: Discussionmentioning
confidence: 99%